Sebelum Jalur Rempah: Awal Interaksi Niaga Lintas Batas di Maluku dalam Perspektif Arkeologi - Marlon NR Ririmasse (Balai Arkeologi Maluku, 2017)
Spice Route has become one of the main issues in the cultural historical studies of Indonesia recently. The discussion is still attached to effort to understand the existence of spice route as the part of the extensive trade system that have been initiated by the history of contact and interaction with the traveler from Western Asia; China; and the European explorers. There were almost no discussion that tried to explore the nature of the spice route prior to the contact with the Mainland Asia and the European. Including in the Maluku Archipelago. This paper discuss the formation process of the spice trade system in the prehistoric period and early historic period in Maluku from the archaeological perspective. The approach that has been adopted in this research is bibliographical studies. This paper found that the trade system and exchange in Maluku has been initiated since the prehistoric period as has been highlighted by the arcaheological studies in the region. Jalur rempah kembali menjadi salah satu isu yang mengemuka dalam diskusi sejarah budaya Nusantara setahun terakhir. Dimana wacana yang mengemuka umumnya masih mengamati keberadaan jalur rempah sebagai jejaring yang dibentuk oleh sejarah kontak dan interaksi dengan para penjelajah dari Asia Barat; Tiongkok dan terutama para pendatang Eropa. Hampir tak ada diskusi yang mencoba mengamati kemungkinan tumbuh kembang jalur niaga ini di era yang jauh lebih awal. Termasuk di Kepulauan Maluku. Makalah ini mencoba mengamati proses pembentukan jaringan niaga dan perdagangan rempah serta aneka komoditi eksotik di masa prasejarah dan awal sejarah di Kepulauan Maluku dari sudut pandang studi arkeologi. Pendekatan yang digunakan adalah kajian pustaka. Hasil kajian menemukan bahwa jaringan niaga dan pertukaran di Maluku telah dibentuk semenjak masa prasejarah sebagaimana ditunjukkan oleh ragam hasil penelitian arkeologi.